2015
DOI: 10.1088/1674-1056/24/9/090304
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of entropic uncertainty in entangled qubits system by local 饾挮饾挴-symmetric operation

Abstract: We investigate the quantum-memory-assisted entropic uncertainty for an entangled two-qubit system in a local quantum noise channel with PT -symmetric operation performing on one of the two particles. Our results show that the quantum-memory-assisted entropic uncertainty in the qubits system can be reduced effectively by the local PT -symmetric operation. Physical explanations for the behavior of the quantum-memory-assisted entropic uncertainty are given based on the property of entanglement of the qubits syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In recent years, parity-time (饾挮饾挴 ) symmetry has attracted increasing attention in non-Hermitian quantum mechanics. [1][2][3][4][5][6][7][8][9][10][11] 饾挮饾挴 -symmetric non-Hermitian systems, which may possess entirely real spectra, [12] have been widely explored in the optical waveguides, resonators, and cold atoms in optical lattices. The exceptional point (EP), known as the 饾挮饾挴 -symmetric phase transition point, indicates the transition between the exact 饾挮饾挴 -symmetric phase and the broken 饾挮饾挴symmetric phase.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, parity-time (饾挮饾挴 ) symmetry has attracted increasing attention in non-Hermitian quantum mechanics. [1][2][3][4][5][6][7][8][9][10][11] 饾挮饾挴 -symmetric non-Hermitian systems, which may possess entirely real spectra, [12] have been widely explored in the optical waveguides, resonators, and cold atoms in optical lattices. The exceptional point (EP), known as the 饾挮饾挴 -symmetric phase transition point, indicates the transition between the exact 饾挮饾挴 -symmetric phase and the broken 饾挮饾挴symmetric phase.…”
Section: Introductionmentioning
confidence: 99%
“…[13] the authors found that the nosignalling principle can be violated when applying the local PT -symmetric operation on one of the entangled particles. More recently, it has also been shown that PT -symmetric operation can be used to suppress the decoherence of amplitude damping model, [14][15][16][17][18][19][20] and slow down the decoherence of pure phase damping model. [21] On the other hand, the entanglement of assistance (EOA) [22,23] as a special case of the localizable entanglement [24] has recently attracted intense attention, [25][26][27][28][29][30][31] which quantifies the entanglement that can be generated between two parties, Alice and Bob, given assistance from a third party, Charlie, when three of them share a tripartite state and where the assistance consists of Charlie initially performing a measurement on his share and communicating the result to Alice and Bob through a one-way classical channel.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Owing to its appealing perfor-mance, the entropic uncertainty relation has attracted much attention. Some quantum operations of quantum states are proposed for stable systems, quantum correlation protection and the reduction of entropic uncertainty, [13][14][15][16][17][18][19] for example, the behavior of QMA-EUR under different noise, the relations between the QMA-EUR and teleportation and entanglement evidence, [20] and the influence of quantum discord and classical correlation on entropic uncertainty in the presence of quantum memory. [21,22] In addition, QMA-EUR has many potential applications in the field of quantum information science, including quantum metrology, [23] quantum transition, [24,25] quantum key distribution, [26] cryptography, and quantum randomness.…”
Section: Introductionmentioning
confidence: 99%